Deformation mechanisms of MMCs under indentation - Pramanik, Alokesh; Zhang, Liangchi; Arsecularatne, Joseph (Elsevier Ltd, 2008)
This paper investigates the deformation mechanisms of MMCs subjected to micro-indentation by a spherical indenter using a three-dimensional finite element modeling. It was found that deformation behavior, hardness and work hardening of MMCs were highly dependant on the location of indentation relative to particles, volume percentage of the particle, and the size ratio of indenter to particle. The hardness of an MMC varied in a complex manner depending on the restriction on the matrix flow by reinforced particles and work hardening of the matrix material. Hardness increased with the increase of volume percentage of reinforced particles and decrease of the size ratio of indenter to particle. Matrix flow due to indentation was highly non-uniform which generated an inhomogeneous strain filed in an MMC. These pose a question that the conventional definition of micro-hardness is not very appropriate for characterizing MMCs.